MOLECULAR MODELS OF ALGINIC ACID: INTERACTIONS WITH CALCIUM IONS AND CALCITE SURFACES - Perry IV T.D.; Cygan R.T.; Mitchell R. (My University, 2006)
Cation binding by polysaccharides is observed in many environments and is important for predictive environmental modeling, and numerous industrial and food technology applications. The complexities of these cation-organic interactions are well suited for predictive molecular modeling and the analysis of conformation and configuration of polysaccharides and their influence on cation binding. In this study, alginic acid was chosen as a model polymer system and representative disaccharide and polysaccharide subunits were developed. Molecular dynamics simulation of the torsion angles of the ether linkage between various monomeric subunits identified local and global energy minima for selected disaccharides. The simulations indicate stable disaccharide configurations and a common global energy minimum for all disaccharide models at ? = 274 ? 7?, ? = 227 ? 5?, where ? and ? are the torsion angles about the ether linkage. The ability of disaccharide subunits to bind calcium ions and to associate with the (10 over(1, ?) 4) surface of calcite was also investigated. Molecular models of disaccharide interactions with calcite provide binding energy differences for conformations that are related to the proximity and residence densities of the electron-donating moieties with calcium ions on the calcite surface, which are controlled, in part, by the torsion of the ether linkage between monosaccharide units. Dynamically optimized configurations for polymer alginate models with calcium ions were also derived.
Keywords: ALGINATE; CALCITE; CALCIUM; DISACCHARIDE; POLYSACCHARIDE